Pengaruh Pembelajaran Pendidikan Kewarganegaraan (PKn) Terhadap Partisipasi Politik Mahasiswa FKIP UNRI - Razali; Erlinda, Sri; Arianto, Jumili (CV Insan Kreasi Media, 2023)
Citizenship education is part of formal education in Indonesia, as well as political education in the context of forming good citizens in carrying out the life of the nation and state. One of the most important points of learning citizenship education is to form good citizens and have political knowledge, especially students as the generation of hope for the nation in influencing the country's political process. This study aimed to see the effect of the Civics course on the political participation of FKIP UNRI students. The research method used in this research is a correlational quantitative research design. Data collection techniques were carried out by field studies (surveys) by distributing questionnaires through the Google form. The data analysis technique used correlation test analysis. The results of this study showed that there was an influence of civics education (PKn) courses on the political participation of FKIP UNRI students based on the results of the correlation test, namely 48.8% in the sufficient category. Its mean that there were 51.2% of other factors that might influence student political participation FKIP UNRI.